Effect of the Harvest Date on the Chemical Composition of Patauá (Oenocarpus bataua Mart.) Fruits from a Forest Reserve in the Brazilian Amazon - Raimundo Silva de Souza; Jerusa Souza Andrade; Suely de Souza Costa (International Journal of Agronomy)
This study aims to evaluate the effect of harvest date on the chemical composition of patauá (Oenocarpus bataua Mart.). Fruits were harvested monthly during the harvest season (June–December, 2009) from native plants in the Adolpho Ducke Forest Reserve located in Manaus, Amazonas, Brazil. The patauá was assessed for pulp yield and chemical composition. Variations in the bunch size, quantity of fruits, chemical constituents and calories occur throughout the season. The pulp yield showed two plateaus, the first from June to September and the second from October to December. The pulp yield was highest in the last three months, the amount of added water equilibrates the total solids and the lipids stood out as the major chemical constituent. At the end of harvest, the patauá became dry and oily and less fibrous. Despite the significant differences, considering that the pulp yield and solids content can be standardized by added water, the entire period of the season may be indicated for the patauá can be periodically collected and considered as a high-energy food for the people of Amazon.